Evaluación de variedades sintéticas de maíz (Zea mays L.) en once ambientes diferentes de Centro América 1991-A - Brizuela, Luis=700 1 Dubón, Teodoro; Campos, Pedro; Reyes R, Roney
Sumario (Es)
5 ref.
Keywords: ZEA MAYS; VARIEDADES; FITOMEJORAMIENTO; EVALUACION; AMERICA CENTRAL